Effects and Long-Term Outcomes of a Modified Triple-P Procedure in Patients With Severe PAS: A Retrospective Cohort Study - Zhao, Huidan; Zhao, Xianlan; Chen, Chen; Tao, Ya; Guo, Ruixia (Frontiers in Medicine, 2022)
Abstract Background: The distinguished Triple-P procedure has been reported as a conservative surgical alternative to peripartum hysterectomy for placenta percreta. In this study, we modified the procedure combined with prophylactic abdominal aorta balloon occlusion and/or tourniquet and evaluated the effect and long-term outcomes. Methods: This was a retrospective study involving pregnant patients with clinically confirmed placenta percreta between January 1st, 2017 and June 30th, 2020 in the First Affiliated Hospital of Zhengzhou University. A total of 334 pregnant women were recruited in this study. The 142 women that were subjected to modified Triple P Procedure were regarded as the observation group while 194 pregnant women that were treated with other sutures were regarded as the control group. Demographic characteristics, placental accreta score, estimated blood loss (EBL), operative time, blood transfusion rate and volume, neonatal weight, post-operative hospital stays and costs were evaluated. Short-term complications, including fever, hematoma, thrombus, bladder rupture and intensive care unit (ICU) transfer rate, as well as long-term outcomes including breast feeding, menstruation, intrauterine adhesion, and chronic abdominal pain among others were followed up in the outpatient clinic and by phone calls. Results: For all cases, EBL in the observation and control groups were 1200 (687 1812) ml and 1300 (800 2500) ml; operative time were 99.5 (84.0 120.0) min and 109.0 (83.8 143.0) min; while lengths of postoperative hospital stays were 4 (4 7) and 5 (4 7) days, respectively. The observation group exhibited significantly better outcomes than the control group. There were no significant differences in placental accreta scores, blood transfusion volume, neonatal weight, fever, hematoma, thrombus, bladder rupture and ICU transfer rates between the two groups. All patients, except one in control group, had preserved uterus. There were no statistically significant differences in short-term and long-term complications between two groups. Conclusion: When combined with prophylactic abdominal aorta balloon occlusion and/or tourniquet, our modified Triple P Procedure is highly effective in reducing hysterectomy and intraoperative blood loss, shortening operative time and hospital stays in placental percreta. However, we should pay attention to short-term and long-term complications, especially to the complications associated with interventional radiology services.